Profitability Stability and Liquidity Risk Mitigation: An Empirical Analysis of Indonesian Guarantee Institutions - Azizah Akbariani Ahmad; Husna Karimah; Muhammad Ariq Athallah Akbar (Fakultas Ekonomi Universitas Warmadewa, 2026)
This study examines the resilience of profitability (Return on Assets) within Indonesian Guarantee Institutions, specifically focusing on withstanding the stress testing triggered by the COVID-19 pandemic. Adopting a quantitative approach, this research analyzed monthly secondary data from the Financial Services Authority (OJK) spanning January 2016 to June 2022 to capture the complete crisis cycle, from the initial stability phase to the subsequent recovery. The data analysis utilized Multiple Linear Regression via the Ordinary Least Squares (OLS) method on 76 observations following data transformation. The empirical results revealed a